Familial Hypodontia: A Case Series - Tangade, S.P.; Ravishankar, T.L.; Batra, M; Shah, A.F. (Kathmandu University Medical Journal, 2017)
The phenomenon of congenitally missing teeth has been described with different names: hypodontia, oligodontia, anodontia, congenitally missing teeth and dental agenesis. The present paper reports familial hypodontia, involving two siblings from a single family. Case I reported the absence of 18, 12, 22 and 31 teeth whereas case II reported the absence of 31 and 41. On the evaluation of the two reported cases that were offspring of same parents and absence of any clinical features associated with any syndrome the final diagnosis of non- syndromic familial hypodontia was made. Both the cases presented agenesis of the teeth leading to malocclusion and aesthetic disturbances. Cases were offered a treatment of interdisciplinary dental approach.